Association study of CREBRF missense variant (rs373863828:G > A; p.Arg457Gln) with levels of serum lipid profile in the Pacific populations. (3rd April 2018) - Ohashi, Jun; Naka, Izumi; Furusawa, Takuro; Kimura, Ryosuke; Natsuhara, Kazumi; Yamauchi, Taro; Nakazawa, Minato; Ishida, Takafumi; Inaoka, Tsukasa; Matsumura, Yasuhiro; Ohtsuka, Ryutaro
Abstract: Background: A missense variant (rs373863828:G > A; p.Arg457Gln) of the CREBRF gene is strongly associated with a higher body mass index (BMI; kg/m 2 ) in Polynesian populations. This variant has also been reported to be associated with lower total cholesterol in Samoans. Aim: The aim of this study is to examine the association of rs373863828:G > A with levels of serum lipids in four Pacific populations. Methods: A total of 613 adult subjects were recruited from Tonga (Polynesians) and the Solomon Islands (Melanesians and Micronesians). Multiple regression analyses adjusted for age and sex were performed to examine the association of rs373863828 with levels of serum lipids in each population. Results: A significant association of rs373863828:G > A with lower level of HDL-cholesterol was detected in the Tonga population ( β = –3.32 and p -value = 0.030). The expected change in HDL-cholesterol with respect to a single copy of the rs373863828-A allele was 3.32 mg/dL. However, the association between rs373863828-A and lower levels of HDL-cholesterol was not significant after further adjustment for BMI in the Tonga population ( β = –2.32 and p -value = 0.13). Conclusions: The rs373863828-A allele may not directly affect the level of serum HDL-cholesterol independent of BMI. To confirm the present findings, association studies with large sample sizes and functional analyses are required.